Pengaruh Manajemen Laba, Asimetri Informasi, Ukuran Perusahaan dan Beta Saham terhadap Cost of Equty Capital: Studi Empiris yang Terdaftar di JII70 Periode (2019–2023) - Sri Rohlan Rogomulyo (Jurnal Ilmiah METHONOMI, 2024)
The objective of this research is to empirically analyze the factors influencing the cost of equity capital in companies listed on the Jakarta Islamic Index (JII) 70 for the years 2019-2023. These factors include earnings management, information asymmetry, company size, and stock beta. The research method used is quantitative, analyzing the company's financial and annual reports. The sampling technique used is purposive sampling with a total of 175 observations. This analysis tool uses Eviews 12. Based on the data analysis, it can be concluded that the earnings management variable does not have a significant effect on the cost of equity capital. Information asymmetry does not affect the cost of equity capital. Company size has a positive effect on the cost of equity capital. Stock beta does not have a significant effect on the cost of equity capital. The implications of this research indicate that companies need to consider factors other than stock beta, such as company reputation, capital structure, or market conditions, when determining funding strategies.